2022
DOI: 10.1002/fam.3049
|View full text |Cite
|
Sign up to set email alerts
|

Fire dynamics inside a large and open‐plan compartment with exposed timber ceiling and columns: CodeRed #01

Abstract: Fire dynamics inside an open-plan compartment with an exposed CLT ceiling and glulam columns: CodeRed #01, Fire and Materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(88 citation statements)
references
References 23 publications
0
68
1
Order By: Relevance
“…There has been very little research conducted in relation to travelling fires in compartments with exposed timber linings, and there is currently no generalised guidance available. In a recent experiment in a large compartment with an exposed CLT ceiling, Kotsovinos et al (2022) found that the temperature profiles beneath the CLT ceiling were unlike the travelling fire methodologies in the literature. Although there have been few tests of mass timber compartments representative of open-plan layouts, recent experiments suggest that burning on ceiling surfaces will increase the fire spread rate and can result in a fully developed fire rather than a travelling fire (Liu & Fischer, 2022).…”
Section: Travelling Firesmentioning
confidence: 89%
See 3 more Smart Citations
“…There has been very little research conducted in relation to travelling fires in compartments with exposed timber linings, and there is currently no generalised guidance available. In a recent experiment in a large compartment with an exposed CLT ceiling, Kotsovinos et al (2022) found that the temperature profiles beneath the CLT ceiling were unlike the travelling fire methodologies in the literature. Although there have been few tests of mass timber compartments representative of open-plan layouts, recent experiments suggest that burning on ceiling surfaces will increase the fire spread rate and can result in a fully developed fire rather than a travelling fire (Liu & Fischer, 2022).…”
Section: Travelling Firesmentioning
confidence: 89%
“…When interior finish materials include wood products (or other combustible materials), there is potential for surface flame spread and additional energy release from the finish materials which may increase the fire growth rate compared to the use of non-combustible finishes. This has been demonstrated by Kotsovinos et al (2022) who conducted an experiment burning wood cribs in a large open-plan compartment with a floor area of 352 m 2 that included a fully exposed CLT ceiling. They found that the rate of fire spread in this experiment was three to eight times faster than in an equivalent non-combustible compartment due to the presence of timber on the ceiling.…”
Section: Fire Growthmentioning
confidence: 96%
See 2 more Smart Citations
“…The most significant effect of increasing the exposed areas of the timber surface in the compartment was a prolonged duration of the fully developed fire phase [24,25]. Kotsovinos et al [26] investigated the fire dynamics of large compartments. The test CodeRed #01 was carried out inside a large open-plan compartment with a floor area of 352 m 2 .…”
Section: Full-scale Fire Testsmentioning
confidence: 99%